Can We Trust Best Practices? Six Cognitive Challenges of Evidence-Based Approaches. (September 2016) - Klein, Devorah E.; Woods, David D.; Klein, Gary; Perry, Shawna J.
There is a growing popularity of data-driven best practices in a variety of fields. Although we applaud the impulse to replace anecdotes with evidence, it is important to appreciate some of the cognitive constraints on promulgating best practices to be used by practitioners. We use the evidence-based medicine (EBM) framework that has become popular in health care to raise questions about whether the approach is consistent with how people actually make decisions to manage patient safety. We examine six potential disconnects and suggest ways to strengthen best practices strategies.